"It Doesn't Have to Be This Way": Hacker Perspectives on Privacy - Steinmetz, Kevin F. (Social justice, 2014)
A study of the attitudes of computer hackers towards computer security, electronic surveillance, and privacy is presented. Topics include hacker ethics, hactivism and the freedom of information; technolibertarianism, technological utopianism and crypto-anarchy; and the role that government, business and individuals have as both protectors of and threats to privacy.